2013
DOI: 10.1155/2013/328934
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Silver Nanoparticles at the Air-Liquid Interface

Abstract: Silver nanoparticles are one of the most prevalent nanomaterials in consumer products. Some of these products are likely to be aerosolized, making silver nanoparticles a high priority for inhalation toxicity assessment. To study the inhalation toxicity of silver nanoparticles, we have exposed cultured lung cells to them at the air-liquid interface. Cells were exposed to suspensions of silver or nickel oxide (positive control) nanoparticles at concentrations of 2.6, 6.6, and 13.2 μg cm−2 (volume concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 59 publications
2
21
0
1
Order By: Relevance
“…The amount of deposited Ag in our study ranged from 0.42 to 2.2 μg cm –2 , depending on the aerosol flow rate (100, 214 and 390 ml min –1 ) and the strength of the electrostatic field (±1 or ±2 kV), based on the results of both gravimetric and chemical analysis (Table ). These amounts are roughly in the same range as in other ALI in vitro studies (Herzog et al , ; Holder & Marr, ) and close to model estimates of relevant exposure levels in humans (Gangwal et al , ). The model by Gangwal et al .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The amount of deposited Ag in our study ranged from 0.42 to 2.2 μg cm –2 , depending on the aerosol flow rate (100, 214 and 390 ml min –1 ) and the strength of the electrostatic field (±1 or ±2 kV), based on the results of both gravimetric and chemical analysis (Table ). These amounts are roughly in the same range as in other ALI in vitro studies (Herzog et al , ; Holder & Marr, ) and close to model estimates of relevant exposure levels in humans (Gangwal et al , ). The model by Gangwal et al .…”
Section: Discussionsupporting
confidence: 84%
“…For instance Herzog et al () reported no increased cytotoxicity (activity of lactate dehydrogenase) after exposing co‐cultured lung cells in ALI to citrate‐coated AgNPs at concentrations of 0.030 and 0.278 μg cm –2 for 4 and 24 h. This is in line with our study showing no effect on membrane integrity. Another study by Holder and Marr () reported only minor cytotoxic and inflammatory responses in A549 cells cultured in ALI when exposed to non‐coated AgNPs at a concentration of 0.7 μg cm –2 for 24 h. One underlying factor for the different results of AgNP toxicity might be that the bioavailability of AgNPs is strongly affected by different extracellular conditions such as pH and the presence of ions, proteins, lipids and other species forming Ag complexes. The bioavailability is also affected by the diverse intracellular conditions in different cellular compartments (Behra et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand in vivo [36] and in vitro [18,19] analysis revealed only minor cytotoxic and inflammatory effects after silver exposure. Furthermore, just recently the authors of a study investigating the effects of Ag NPs at the air-liquid interface found only a negligible cytotoxic and minor inflammatory response [46]. On the other hand Ag-NP toxicity was reported by many others whereas ROS dependent DNA damage, anti-proliferative effects, increase of inflammatory markers and subsequent cytotoxicity was observed in vitro [15,17,19,20,27,47] and in vivo [35,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Since the calculated amount of antioxidants adsorbing onto particles is small compared to the measured depletion, oxidative loss by ROS is presumed to be the dominant mechanism. 58 However, Ag, TiO 2 , and C 60 are of concern because they can catalyze the formation of high amounts of furans 9 or perhaps other pollutants that are more genotoxic. Oxidation of GSH by oxygen over 1 h is a less likely explanation as it requires pH greater than 8.5 and copper salt as a catalyst.…”
Section: Limitationsmentioning
confidence: 99%